ANALYSIS OF INFORMATION ON THE INFLUENCE OF VACCINE ON THE LEVEL OF PARTICIPATION OF COVID-19 VACCINATION IN VARIOUS PUSKESMAS IN NTT PROVINCE - Sidarta Sagita; Maria Agnes E. Djeha; I Made Artawan (The Islamic Education and Multiculturalism Foundation, 2023)
Public knowledge about COVID-19 and vaccines can support the success of programs to deal with this disease. The scope of providing vaccine information in Indonesia is not maximized because it is still new and some people refuse to be vaccinated for reasons of worry about the safety and effectiveness of vaccines, they express distrust of vaccines and question the halalness of vaccines . To find out Information Analysis About the Effect of Vaccines on the Participation Rate of Covid-19 Vaccination at Various Health Centers in NTT Province . Obtain research knowledge regarding the influence of Information Analysis on the Effect of Vaccines on the Participation Rate of Covid-19 Vaccination at Various Health Centers in the Province of NTT. This research is also useful for helping research subjects increase their knowledge and insight into knowledge by participating in the COVID-19 vaccination at various NTT Provincial Health Centers .